(untitled) (Scientific journal of the Fergana State University, 2024)
The article considers the chemical composition of biologically active substances contained in the fennel plant (Pimpinella anisum L.) grown in Uzbekistan, its medicinal properties, as well as its use in folk medicine, modern medicine, and also with the help of the method of autoxidation of adrenaline in “in vitro" conditions, the oxidation activity of the plant is revealed.